Control of Plasmid Replication in Escherichia coli: Correlation of the Membrane Site of DNA Replication with the Bacterial Segregation Unit - Korn, D. (1971)
The fate of parental λ genomes after superinfection of homoimmune lysogenic cells was studied. The data confirm a previous observation that in the presence of the λ repressor, superinfecting λ DNA does not become associated with replication sites on the bacterial cell membrane. Under these conditions, the nonreplicating, superinfecting phage genomes do not become associated with the bacterial segregation unit. These results support the concept that the attachment of DNA to the bacterial membrane at specific sites is involved in the control of both chromosome replication and segregation, as predicted by the replicon hypothesis.